Teacher and Students’ Politeness Strategies in EFL Classroom Interactions - Santi Fitriyani; Erna Andriyanti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This study aims to explore the use of politeness strategies which occur in EFL classroom interactions in a senior high school. This study applied a descriptive qualitative research design to explore the politeness strategies used by the teacher and the students in their interactions. The participants in this study were an English teacher and 30 students. The data in this study were in the form of utterances which contain politeness strategies. The data were taken from a 90-minutes English lesson which was video-recorded. The findings showed there were a total of 13 excerpts containing three politeness strategies: positive politeness strategy, negative politeness strategy, and bald-on-record strategy. The interactions were dominated by the teacher. Moreover, the politeness strategies which occurred in the classroom interactions were influenced by some factors such as age difference, institutional position, power, and social distance.